(untitled) (AYUSHDHARA, 2017)
Ginger, (Zingiber officinale Roscoe) is one of the important medicinal plants which is being used in Ayurveda from the ancient time. Zingiber officinale is well known as a health promoting. It has been an important ingredient in Ayurvedic, Chinese, and Tibb-Unani herbal medicines. In ancient culture medical practitioners focused on herbals for the promoting the immune system of body. Ginger has been identified as prostaglandin synthesis suppressor through inhibition of cyclooxygenase-1 and cyclooxygenase-2 and apart from its medicinal properties ginger can also be used as an antioxidant supplement. It has also anti-oxidant, anti-inflammatory, anti bacterial, immune modulator, anticancer, anti-diabetic and several properties. It has a rich phytochemical compound like Gingeral, Shogaol, Zingerene. In Pranavaha srotas anti-inflammatory effect is very useful to treat the disease Ginger inhibits the production of free radicals like ketone bodyH+,OH-, Lactic acid, uric acid intermediated product which is leading cause of DNA damage and various disease. Ethenol extract of Z.officinale alone with vit-E induced the nephro toxicity and Acetaminophen induced liver cell damage. Studies have shown that, the long term dietary intake of ginger has hypoglycaemic and hypolipidaemic effect It can reduced the muscle pain after physical activity, valuable ingredients which can prevent various cancer’s angiogenesis and metastasis induction of apoptosis and inhibit of cell-cycle progression and used in the cardiovascular system, Diabetes mellitus and Gastrointestinal rheumatism, cough, corhyza and bronchitis disease. Aim of this article to provide knowledge about Anti-oxidant and Anti-inflammatory properties of Zingiber officinalis.